2002
DOI: 10.1081/pfc-120004472
|View full text |Cite
|
Sign up to set email alerts
|

Development of Elisa Technique for the Analysis of Atrazine Residues in Water

Abstract: A highly sensitive enzyme immunoassay is described for the detection of atrazine residues in water. Atrazine derivative was conjugated to Bovine Serum Albumin (BSA) to obtain an immunizing antigen and to Horseradish Peroxidase enzyme (POD) to obtain a marker for immunoassay. The formation of these conjugations was confirmed by UV spectroscopy as well as by gel-electrophoresis. Polyclonal antibodies were raised in rabbits by immunization with an atrazine-BSA conjugate containing 29 atrazine residues per BSA mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, current techniques have several limitations when considered for such an application. For instance, ELISAs have become popular for the on-site screening of environmental samples; however, these methods have only moderate accuracy and precision and give a result that is affected by any compound that binds to the antibodies they employ as reagents. GC and HPLC are more accurate and precise but generally involve laboratory-based methods that require the transport and storage of large quantities of sample. In addition, GC and HPLC often require several sample pretreatment steps (e.g., derivatization or solid-phase extraction) for environmental analytes that may result in additional products, coextracted interferences, or contaminants from the pretreatment step. , Furthermore, the lag between the time of sample collection and analysis in these methods is of concern, since some herbicides can have a large and rapid change in concentration during high-use seasons (e.g., during or following their application)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, current techniques have several limitations when considered for such an application. For instance, ELISAs have become popular for the on-site screening of environmental samples; however, these methods have only moderate accuracy and precision and give a result that is affected by any compound that binds to the antibodies they employ as reagents. GC and HPLC are more accurate and precise but generally involve laboratory-based methods that require the transport and storage of large quantities of sample. In addition, GC and HPLC often require several sample pretreatment steps (e.g., derivatization or solid-phase extraction) for environmental analytes that may result in additional products, coextracted interferences, or contaminants from the pretreatment step. , Furthermore, the lag between the time of sample collection and analysis in these methods is of concern, since some herbicides can have a large and rapid change in concentration during high-use seasons (e.g., during or following their application)…”
mentioning
confidence: 99%
“…For instance, ELISAs have become popular for the on-site screening of environmental samples; however, these methods have only moderate accuracy and precision and give a result that is affected by any compound that binds to the antibodies they employ as reagents. [16][17][18] GC and HPLC are more accurate and precise but generally involve laboratory-based methods that require the transport and storage of large quantities of sample. In addition, GC and HPLC often require several sample pretreatment steps (e.g., derivatization or solid-phase extraction) for environmental analytes that may result in additional products, coextracted interferences, or contaminants from the pretreatment step.…”
mentioning
confidence: 99%
“…In many previous studies polyclonal antisera as such have been used for estimat- ing the levels of different pesticides [18][19][20][21][22][23]. In the present study, we have demonstrated the use of highly purified antibodies using a combination of Protein-A sepharose column followed by passing through carrier protein column.…”
Section: 4mentioning
confidence: 82%
“…Immunoassays can meet these requirements. Numerous related methods for the detection of atrazine have been reported, such as enzyme-linked immunosorbent assay (ELISA) [10][11][12][13][14][15], colloidal gold-based immunochromatographic (ICG) strip assay [16][17][18], time-resolved fluorescent immunoassay (TRFIA) [19] and liposome immune lysis assay (LILA) [20]. The specific features of each study are listed and compared in Table 1.…”
Section: Introductionmentioning
confidence: 99%